Takhrij and Syarah Hadith of Agrotechnology Benefits of Mushroom al-Kam'ah - Hadi Muhammad Ziyanul Haque; Wahyudin Darmalaksana; Windhy Chandria (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this study stated that the Al-Kam'ah plant was the herbal medicine recommended by the Prophet for eye treatment. The conclusion of this research is tahkrij and syarah hadith which contain the Al-Kam'ah plants which are beneficial for eye health